PENGARUH PENGALAMAN AUDITOR, KOMITMEN PROFESIONAL, TEKANAN KETAATAN DAN NILAI ETIKA ORGANISASI TERHADAP PERSEPSI PERTIMBANGAN ETIS (Studi Empiris Pada Kantor BPKP – RI Perwakilan Provinsi Riau) - Sary, Desy Ratna; Hasan, Amir; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the impact of the experience of auditors, professional commitment, obedience pressure, and ethical values of the perception of ethical considerations organizations using multiple regression analysis.The aim of this study is the Financial and Development Supervisory Agency Representative Riau Province. This research is a survey method. Respondents in this study is the auditor BPKP-RI Representative Riau Province. The number of samples was 82 auditors. There are five variables in this study consisted of four independent variables namely the auditor's experience, professional commitment, obedience pressure, and ethical values of the organization, and the dependent variable is the perception of ethical considerations. According to the research results, it can be concluded that professional commitment, obedience pressure and the value of the organization's ethics significantly affect the perception of ethical considerations, while the auditor's experience did not significantly affect the perception of ethical considerations. The coefficient of determination indicates that the auditor's experience, professional commitment, obedience pressure, and ethical values of the organization affect the dependent variable (the perception of ethical considerations) of 45.4%, while 54.6% is influenced by others factors.Keywords: auditor's experience, professional commitment, obedience pressure, ethical values of the organization's and perception of ethical consideration.